An evaluation of the alleys of Glodok and its market culture - Budianto, Valary; Tadeus, Redemptsia Quinn Elsa; Djaukar, Jeanette; Sugangga, Marissa; Ekomadyo, Agus Suharjono (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
Glodok is considered one of the largest Chinese urban areas in Indonesia, featuring shops, dwellings, temples, alleyways, and various other elements of Chinese culture. Several local urban practices can also be identified, including selling and buying, as well as the house-shop relations that are accomplished through the spaces between the buildings or the alleys. The people act as active agents of spatial production in everyday life in this location, supporting their economic, social, and cultural activities. To investigate the interrelationship between Chinese-Indonesian market culture and its influence on interiority, literature studies, and ethnography methods were practiced. The results of the study showed three main aspects affecting the interiority of Glodok, namely the 3-dimensional space of the alleys, the cultural identity, and the activity of the people, as well as experiences. Furthermore, the interiority is manifested in the activity of each individual and experiences within the alley, which exists due to market culture. Through an architectural approach that focuses on accommodating the local tradition, culture, and beliefs, the ambience present in Glodok causes both the people and visitors to unintentionally think about nostalgic experiences and memories, thereby creating an emotional, cultural, and historical engagement.